Brucella invasion of human intestinal epithelial cells elicits a weak proinflammatory response but a significant CCL20 secretion - Ferrero, Mariana Cristina (2012)
In spite of the frequent acquisition of Brucella infection by the oral route in humans, the interaction of the bacterium with cells of the intestinal mucosa has been poorly studied. Here, we show that different Brucella species can invade human colonic epithelial cell lines (Caco-2 and HT-29), in which only smooth species can replicate efficiently. Infection with smooth strains did not produce a significant cytotoxicity, while the rough strain RB51 was more cytotoxic. Infection of Caco-2 cells or HT-29 cells with either smooth or rough strains of Brucella did not result in an increased secretion of TNF-alpha, IL-1beta, MCP-1, IL-10 or TGF-beta as compared with uninfected controls, whereas all the infections induced the secretion of IL-8 and CCL20 by both cell types. The MCP-1 response to flagellin from Salmonella typhimurium was similar in Brucella-infected or uninfected cells, ruling out a bacterial inhibitory mechanism as a reason for the weak proinflammatory response. Infection did not modify ICAM-1 expression levels in Caco-2 cells, but increased them in HT-29 cells. These results suggest that Brucella induces only a weak proinflammatory response in gut epithelial cells, but produces a significant CCL20 secretion. The latter may be important for bacterial dissemination given the known ability of Brucella to survive in dendritic cells.